Strategi Pembelajaran untuk Anak Usia Dini - Suci Rahmadani; Alva Mawadda; Gusmaneli Gusmaneli (STIKes Ibnu Sina Ajibarang, 2024)
Learning strategy is needed for optimal learning process according to planning. Educators have an enormous influence on the growth and development of children's intelligence. The principles of early childhood learning are goal-oriented, activity, individuality, integrity, interactive, inspirational, fun, challenging, motivational.